2019
DOI: 10.1111/luts.12256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistive index of the prostate and bladder sonomorphologic parameters as replacements for urodynamics to predict bladder outlet obstruction in patients with lower urinary tract symptoms suggestive of benign prostatic hyperplasia

Abstract: Objective: This study investigated whether the resistive index (RI) of prostate and bladder sonomorphologic parameters (total prostate volume [TPV], detrusor wall thickness [DWT], intraprostatic protrusion [IPP]) can be used instead of urodynamic studies (UDS) to predict bladder outlet obstruction (BOO) in benign prostatic hyperplasia (BPH) with lower urinary tract symptoms (LUTS). Methods: Men aged ≥50 years with clinical BPH/LUTS were prospectively enrolled included. Basic evaluations, measurement of sonomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A collective result of low RoB study group including only 3 studies [11, 18, 21] evaluating UEBW indicated that there was slightly increase in SSY to 0.931 (95% CI, 0.885–0.963; I 2 = 25.5%) and SPY to 0.796 (95% CI, 0.718–0.860; I 2 = 89.9%). Combined results from 9 studies [7, 10, 12-14, 17, 19, 20, 22] with low RoB evaluating DWT did not obviously change the accuracy, with combined SSY of 0.655 (95% CI, 0.615–0.693; I 2 = 89.9%) and SPY was 0.907 (95% CI, 0.877–0.931; I 2 = 74.3%). Considering the measure methods, 1 study [15] using the corrected UEBW were excluded.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…A collective result of low RoB study group including only 3 studies [11, 18, 21] evaluating UEBW indicated that there was slightly increase in SSY to 0.931 (95% CI, 0.885–0.963; I 2 = 25.5%) and SPY to 0.796 (95% CI, 0.718–0.860; I 2 = 89.9%). Combined results from 9 studies [7, 10, 12-14, 17, 19, 20, 22] with low RoB evaluating DWT did not obviously change the accuracy, with combined SSY of 0.655 (95% CI, 0.615–0.693; I 2 = 89.9%) and SPY was 0.907 (95% CI, 0.877–0.931; I 2 = 74.3%). Considering the measure methods, 1 study [15] using the corrected UEBW were excluded.…”
Section: Resultsmentioning
confidence: 94%
“…SROC curves for SSY and SPY and publication bias plot are exhibited in Figures 4 and 5. Totally 10 studies [7, 10, 12-14, 16, 17, 19, 20, 22] and 1,204 participants were included in our analysis concerning about DWT. Data shown in Table 3 performs that the pooled SSY for DWT for BOO diagnose was 0.68 (95% CI, 0.56–0.78) and SPY was 0.91 (95% CI, 0.82–0.96) with I 2 values of 93%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostatic volume was also not correlated with contractility. The correlation between prostatic volume and urodynamic obstruction is still unclear with conflicting results between studies 19–21 . Sullivan and Yalla study in 1996 showed a significant increase in detrusor isometric pressure with the degree of urodynamic obstruction, 22 so contractility seemed to depend more on urodynamic obstruction than on anatomical obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between prostatic volume and urodynamic obstruction is still unclear with conflicting results between studies. [19][20][21] Sullivan and Yalla study in 1996 showed a significant increase in detrusor isometric pressure with the degree of urodynamic obstruction, 22 so contractility seemed to depend more on urodynamic obstruction than on anatomical obstacle. In daily practice, the measurement of contractility by stop-test tends to be replaced by nomograms applied to pressure-flow study data, such as the International Continence Society nomogram and the BCI, which are easier to perform.…”
Section: Discussionmentioning
confidence: 99%